경북 일부 지역 요리학원 수강생의 교육환경에 따른 학습 만족도 - 이인숙(In-Sook Lee) (東아시아食生活學會誌, 2011)
The purpose of this study was to analyze the association between educational environment (physical environment of cooking institutes and curriculum) and satisfaction with learning of students at local cooking institutes. Self-administered questionnaires were distributed to 300 student enrolled at cooking institutes located in Pohang and Gyeongju, and a total of 265 were usable. Collected data were statistically analyzed using SPSS 12.0 by frequency, factor, reliability, t-test and Duncan's multiple range test. The results can be summarized as follows. Most of the subjects were enrolled at cooking institutes to learn Korean and Western cuisine. There were significant differences in learning according to institution, facility, method and instructor. There were also significant differences in learning according to gender, age, education, and attended classes. Based on the results, the physical environment of cooking institutes contributed to learning in the students, but the operation system also needs to be improved. However, study was limited in sample size and area, the results can-not be generalized.